The Effectiveness of NIK–NPWP Integration and Transaction Digitalization on Underreporting: The Role of Financial Literacy among MSME Actors - Irmawati Alimuddin; Andriani Saputri; Fithriah Musadat (Universitas Muhammadiyah Prof. DR HAMKA., 2026)
This study examines the effect of NIK-NPWP integration and transaction digitalization on underreporting among MSME actors in Baubau City, while testing financial literacy as a moderating variable. The research employed a quantitative survey design involving 228 MSME actors with active tax numbers and business legality. Data were gathered through a structured questionnaire and analysed using multiple linear regression and moderated regression analysis with SPSS 26. The results show that NIK-NPWP integration and transaction digitalization significantly affect the underreporting score. However, both estimated coefficients are positive, meaning that the hypothesised direct reduction in underreporting is not confirmed by the model signs and must be interpreted cautiously in light of instrument coding and implementation context. Financial literacy is not supported as a significant moderating variable because the interaction terms are not significant at the 5 percent level. Theoretically, this study extends the application of the Theory of Planned Behavior and the Technology Acceptance Model by placing tax-identity integration and transaction digitalization in the underreporting setting. Practically, the findings imply that digital tax reform needs stronger socialization, service quality, and bookkeeping assistance before it can consistently suppress underreporting among MSMEs